A new malaria vector in Africa: Predicting the expansion range of Anopheles stephensi and identifying the urban populations at risk - Sinka, M E; Pironon, S; Massey, N C; Longbottom, J; Hemingway, J; Moyes, C L; Willis, K J (Proceedings of the National Academy of Sciences - PNAS, 2020)
In 2012, an unusual outbreak of urban malaria was reported from Djibouti City in the Horn of Africa and increasingly severe outbreaks have been reported annually ever since. Subsequent investigations discovered the presence of an Asian mosquito species; , a species known to thrive in urban environments. Since that first report, has been identified in Ethiopia and Sudan, and this worrying development has prompted the World Health Organization (WHO) to publish a vector alert calling for active mosquito surveillance in the region. Using an up-to-date database of published locational records for across its full range (Asia, Arabian Peninsula, Horn of Africa) and a set of spatial models that identify the environmental conditions that characterize a species' preferred habitat, we provide evidence-based maps predicting the possible locations across Africa where could establish if allowed to spread unchecked. Unsurprisingly, due to this species' close association with man-made habitats, our maps predict a high probability of presence within many urban cities across Africa where our estimates suggest that over 126 million people reside. Our results strongly support the WHO's call for surveillance and targeted vector control and provide a basis for the prioritization of surveillance.